Tradisi Je’ne-Je’ne Sappara Di Desa Balangloe Kecamatan Tarowang Kabupaten Jeneponto Perspektif Hukum Islam - Irsan R; Abdul Halim Talli (Universitas Islam Negeri Alauddin Makassar, 2021)
The aims of this study are: (i) to find out how the local community views the Je'ne-Je'ne Sappara tradition. (i) From this study, we can find out how the views of Islamic law are on the Je'ne-Je'ne Sappara traditional ceremony in Balangloe village, Tarowang sub-district, Jeneponto district. The type of this research is classified as field research or field research that is descriptive in nature with the research approach used: the syar'i approach, and the social/sociological approach. namely, observation, interviews, and documentation. The results of the study will produce the following: (1) The je'ne-je'ne sappara tradition procession is carried out in the month of safar, which is when you enter 7 trips to 14 trips every year. It is held on the seaside of the village of Balagloe Tarowang for 7 days and 6 nights. (2) The people of Balagloe Tarowang strongly adhere to the traditions of their ancestors, people believe that when they do not carry out the tradition, they will get reinforcements or disaster, this act has violated Islamic law because they believe in something outside the provisions of Allah swt.Keywords: Tradition; Sappara; Islamic Law